2011
DOI: 10.1080/19475705.2010.536263
|View full text |Cite
|
Sign up to set email alerts
|

Seismotectonics at the terminal ends of the Himalayan Arc

Abstract: The Himalayan arc has an arcuate E-W trending geometry with reversal of trend at the terminal ends -Nanga-Parbat (western) syntaxis and Namcha-Barwa (eastern) syntaxis. Both ends are characterized by an actively deformed uplifted dome with its flanks bounded by active shear zones/faults that cause the majority of the seismicity. Compiled map data and seismo-geological depth sections around these two syntaxial zones have brought out active crustal structure and seismotectonic setup. The Nanga-Parbat syntaxis ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…These patches may be correlated with mass flowage of mobile rocks and creation of small magmatic pockets by possible decompressional melting. The thickening of the crust is also noteworthy (see sections in Mukhopadhyay et al, 2011) and the exhumation is caused by erosion along the Siang River with crustal scale folding at a rate of w10 mm/yr (Burg et al, 1998). Such zone with extreme horizontal and vertical movement is an ideal candidate for stress accumulation and release and thus characterized by recurrent earthquake swarm activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These patches may be correlated with mass flowage of mobile rocks and creation of small magmatic pockets by possible decompressional melting. The thickening of the crust is also noteworthy (see sections in Mukhopadhyay et al, 2011) and the exhumation is caused by erosion along the Siang River with crustal scale folding at a rate of w10 mm/yr (Burg et al, 1998). Such zone with extreme horizontal and vertical movement is an ideal candidate for stress accumulation and release and thus characterized by recurrent earthquake swarm activity.…”
Section: Discussionmentioning
confidence: 97%
“…1) of the eastern Himalayan Syntaxial region (27 e31 N, 92 e99 E) shows the tectonic set up of the area Figure 1. Seismotectonic map of area in and around the eastern Himalaya Syntaxis (compiled after Lee et al, 2003;Mukhopadhyay et al, 2011;Xu et al, 2012) B. Mukhopadhyay, S. Dasgupta / Geoscience Frontiers xxx (2015) 1e8 2 (compiled after Lee et al, 2003;Mukhopadhyay et al, 2011;Xu et al, 2012) with earthquake data (M 4) for the period 1964 to 2011 of reviewed ISC Bulletin. Local seismic network data are not available to the authors.…”
Section: Earthquake Clustermentioning
confidence: 99%
“…Seismic activity is related to north-south vergence of Indian and Asian plates. Our previous study (see figure 5(a) of Mukhopadhyay et al 2011b) has also indicated activation of an out-of-sequence (?) thrust west of Gilgit in this segment that is producing the bulk of present seismicity.…”
Section: Kohistan Arc (Zone a Of Figure 3(a))mentioning
confidence: 91%
“…4.0 within time domain 1964-2010) on tectonic elements (after Dasgupta et al 2000) are carried out ( figure 3(a)). The plot and our previous analysis (Mukhopadhyay et al 2011a(Mukhopadhyay et al , 2011b have brought out five distinct seismotectonics zones (A-E of figure 3(a)) where earthquake dominantly clusters -from west to east, they are Kohistan arc (A); Kashmir-Hazara Syntaxis (B); Nanga-Parbat (Western Syntaxis) (C); Karakoram (D) and Himachal Himalaya (E). Further evaluation is carried out through seismo-geological cross sections; which are drawn with earthquake EHB relocated parameters, topography and surface geology to understand the plate configuration in conjunction to the known seismo-tectonic model of the Himalaya.…”
Section: Seismotectonic Evaluationmentioning
confidence: 98%
“…The pattern of basin depth variation is usually explained by stronger subduction along the HFT and generation of larger accommodation space [5][6][7] , for fluvial sediment deposition. The northern fringe is closed by the Mishmi Hills, which is in syntaxial relationship 8 with the NPT. The southern fringe is bound by the Mikir Hills which is supposedly the northern extension of Shillong massif 9 .…”
mentioning
confidence: 99%